Leadership with impact preparing health and human service practitioners in the age of innovation and diversity - Araque, Juan C. (Juan Carlos); Weiss, Eugenia L. (New York, NY Oxford University Press, 2019)
"This book offers new ways of thinking and approaching complex problems through a conceptual and practical leadership approach founded on innovation and diversity. The I.D.D.E.A. Leadership Framework is introduced the goal of assisting health and human service practitioners with their design, implementation, and evaluation of innovative programs to help vulnerable populations and promote social change"--
The power of innovation in organizational and social change -- Key leadership styles for social change and innovation -- Team work, collaboration, and motivation -- Communication strategies and leadership -- Networking, community partnerships and social media messaging -- Race and ethnicity: past and present -- Cultural proficiency, equity, and diversity -- Women in leadership -- Organizational strategic planning -- Leadership and effective supervision -- Conflict resolution strategies -- Leadership and crisis response -- Avoiding burnout: promoting job engagement and satisfaction -- The mindful leader -- Assessing interventions and evaluating programs -- Putting it all together: application of the I.D.D.E.A. leadership framework to achieve social change.
Includes bibliographical references and index.
Keywords: Health services administration; Leadership; Social work administration; Human services personnel -- Supervision of; Public health personnel -- Supervision of